Practical guide to occupational health and safety - Erickson, Paul A., 1941-
Written with corporate regulatory compliance officers, health and safety managers, loss control managers, and human resource specialists in mind, this book offers workplace-tested strategies for meeting the health and safety needs of a modern corporation. Emphasizing the practical means of achieving compliance with OSHA regulations, this book also provides a unique assessment of the more extensive factors that influence the management of workplace health and safety. The integration of practical regulation strategies with corporate objectives is particularly relevant to graduate curricula in bu.